Zeitschrift für Bankrecht und Bankwirtschaft : Journal of Banking Law and Banking (JBB) (RWS-Verlag, 1989)
The ZBB is published bi-monthly and, in this form, is a unique research forum with an interdisciplinary programme. It reaches jurists and economists from research and practice and conveys the knowledge provided by proven experts. The ZBB combines well-founded practical knowledge at the highest level with top-class research. The themes are discussed in-depth which is exactly what like-minded people want. The readers profit from this: An article in the ZBB provides information about an issue or a current theme in such a thorough manner that the acquired knowledge can be directly applied in one's daily work. Technical information like it should be. Through an anonymous assessment procedure, the ZBB ensures that the quality remains consistently high and that the articles are unbiased. In the diversity of the articles, research and practice in banking law are competently combined. The ZBB brings documentation from the banking industry and banking law policies in real-time and comments on important fundamental rulings - the court ruling being discussed is respectively also published. Upon a supplemental basis, a comprehensive overview of jurisprudence is provided as guiding principles with references to the sources from other journals.